Identification of a Dual Inhibitor of Secreted Phospholipase A2 (GIIA sPLA2) and SARS-CoV-2 Main Protease - Maria A. Theodoropoulou; Giorgos S. Koutoulogenis; Linlin Zhang; Ifigeneia Akrani; Emmanuel Mikros; Rolf Hilgenfeld; George Kokotos (MDPI AG, 2022)
The development of novel agents to combat COVID-19 is of high importance. SARS-CoV-2 main protease (Mpro) is a highly attractive target for the development of novel antivirals and a variety of inhibitors have already been developed. Accumulating evidence on the pathobiology of COVID-19 has shown that lipids and lipid metabolizing enzymes are critically involved in the severity of the infection. The purpose of the present study was to identify an inhibitor able to simultaneously inhibit both SARS-CoV-2 Mpro and phospholipase A2 (PLA2), an enzyme which plays a significant role in inflammatory diseases. Evaluating several PLA2 inhibitors, we demonstrate that the previously known potent inhibitor of Group IIA secretory PLA2, GK241, may also weakly inhibit SARS-CoV-2 Mpro. Molecular mechanics docking and molecular dynamics calculations shed light on the interactions between GK241 and SARS-CoV-2 Mpro. 2-Oxoamide GK241 may represent a lead molecular structure for the development of dual PLA2 and SARS-CoV-2 Mpro inhibitors.